Analisis Struktur Kinerja dan Konsep Keunggulan Komparatif Industri - Melinda Wirastiti; Aditya Arga Widhyasa; Muhammad Yasin (Universitas 45 Surabaya, 2024)
Industry is a crucial sector in a country's economy because it contributes significantly to economic growth, job creation and social welfare. This article aims to analyze the structure of industrial performance and the concept of comparative advantage in Indonesia. The industry performance structure is evaluated based on allocative efficiency, technical efficiency, inflation effects, equality, technological progress, product quality, employment opportunities and profits. The concept of comparative advantage explains that a country gains advantages by specializing in the production and export of goods or services that have relatively lower production costs compared to other countries. This analysis focuses on various factors that influence industry performance, such as the number and size of companies, level of product differentiation, market entry and exit barriers, government policies, macroeconomic conditions, technological developments, and globalization. By implementing comparative advantage strategies, such as production efficiency, developing workforce skills, and improving infrastructure, it is hoped that it can increase the competitiveness of Indonesian industry in the global market. This article provides strategic recommendations to improve the performance and competitiveness of Indonesian industry, including the importance of specialization, increased market access, and industrial collaboration.